Spring 97 : Jong Talent in Antwerpen. - Van Der Auwera, Maarten; De Decker, Daan; Francken, Marc; Gildemijn, Marie-Pascale; Herreman, Kris; Holsbeek, Dan; Paulus, Camille; Pirotte, Philippe; Van Eetveldt, Anja; Vandenhoucke, Sylvie; Walgrave, Jan (Antwerpen : Provincie Antwerpen, 1997)
Benhelima, Charif ; Boonen, Anne Mie ; De Blende, Wim ; De Decker, Daan ; François, Kurt ; Geuens, Jan ; Herreman, Kris ; Jacobs, Marco ; Johansen, Siv-Bente ; Lauwers, Masja ; Lavickova, Lucie ; Jiraskova, Klara ; Meyers-Boelens ; Mondelaers, Iris ; Najd Javadipour, Maryam ; de Beeck, Hans Op ; Robijns, Gert ; Vandenhoucke, Sylvie ; Van Eetveldt, Anja ; Van Gestel, Liesbeth ; Van Hees, Franklin ; Van In, Erik ; Van Obberghen, Vanessa ; Vendéraz ; Vindevogel, Tine ; Wright, Cindy
biog. per kunstenaar
Spring 97 : Jong Talent in Antwerpen, Koningin Fabiolazaal, Antwerpen, 15 april - 1 mei 1997
Nederlands
boek
Keywords: Antwerpen